A 14+7 day quarantine period and a dual nucleic acid testing reagent strategy detect potentially indiscoverable Coronavirus disease 2019 infections in Xiamen, China - Wang, Yong-Jing; Xue, Jian-Hang; Fang, Zan-Xi; Xie, Jia-Wen; Niu, Jian-Jun; Yang, Tian-Ci; Lin, Li-Rong (Clinica chimica acta, 2022)
•The probability of detection during the 14-day was higher than that during the 7-day.•The 14-day quarantine period is not sufficient to detect all COVID-19 patients.•When the two reagents were used in parallel, the detection rate reached 100%. Determining what quarantine period and detection strategy are more effective and sustainable remains a challenge for further prevention and social stability. From October 2020 to December 2021, 290,547 inbound overseas travelers were subject to government quarantine in Xiamen, China. The detection rate of COVID-19 during different quarantine periods using dual or single nucleic acid testing reagents. The COVID-19 positive rate was 1.79% (519/290,547). The detection rates during the 7-day, 14-day and 14+7-day quarantine periods using the dual reagents were 78.4%, 91.7%, and 100%, respectively. The detection rate of the 7-day, 14-day and 14+7-day quarantine periods were 73.99%, 86.51%, and 94.22%, respectively, using the Liferiver reagent and 72.25%, 84.59%, and 91.91%, respectively, using the Daan reagent. Based on the 14+7 day strategy, dual nucleic acid testing reagent strategy detected all imported cases, but 30 cases (5.78%) were not detected via Liferiver reagent and 42 (8.09%) cases not detected via Daan reagent. A 14+7-day quarantine period and dual nucleic acid testing reagent strategy are effective screening methods for COVID-19 among inbound overseas travelers. The superior detection rate of these strategies reduce the risk of secondary transmission of the SARS-CoV-2 virus.